Policies, laws, and regulations in support of farmer-managed seed systems: still a long way to go. A review of 14 countries in Africa - Vernooy, Ronnie; Adokorach, Joyce; Kimani, Dominic; Marwa, Anna; Mayoyo, Alfios; Nyadanu, Daniel (2023)
The main finding of this review report of seed (related) policies and laws in 14 African countries is that, although in most countries there is some form of acknowledgment that farmer-managed seed systems exist, there are not many positive results related to recognition of and concrete support for farmer-managed seed systems (policy, legal, technical, operational, and financial support). Much remains to be done to promote and support the use of diverse genetic resources for climate change adaptation, e.g., through the strengthening of national and (sub)regional collaboration on integrated seed sector development and more support for farmer-managed seed system activities, such as community seed banking and local seed business development. Inspiring examples of new practices can be found in many countries, spearheaded by civil society and in a few cases supported by governments, which can serve as examples to inform and reform existing seed (related) policies and laws.